Antworten:
Der Wert ist #-2#
Erläuterung:
Lassen # x = (2 + sqrt5) ^ (1/3) + (2-sqrt5) ^ (1/3) # dann
# x ^ 3 = {(2 + sqrt5) ^ (1/3) + (2-sqrt5) ^ (1/3)} ^ 3 #
Erinnerung:
# (a + b) ^ 3 = a ^ 3 + b ^ 3 + 3ab (a + b), a ^ 2-b ^ 2 = (a + b) (a-b) #
und lass # a = (2 + sqrt5), b = (2-sqrt5):. ab = 4-5 = -1 #
x: 3 = (2 + sqrt5) ^ (3 · 1/3) + (2 sqrt5) ^ (3 · 1/3) + 3 (2 + sqrt5) (2 sqrt5) (2 + sqrt5) + 2-sqrt5) #
oder # x ^ 3 = 2 + stornieren (sqrt5) + 2-stornieren (sqrt5) +3 (4-5) (2 + stornieren (sqrt5) + 2-stornieren (sqrt5)) #
oder # x ^ 3 = 4 + 3 (-1) (4) oder x ^ 3 = 4 -12 oder x ^ 3 = -8 # oder
#x = (-8) ^ (1/3) = -2 #. Der Wert ist #-2# ANS